Informal learning sector in the African context:The role of trust in human resource management - (:unkn) unknown (My University, 2020)
The aim of this research is to show that human resource managementpractices in informal learning are implemented through the lens of trust.The aim is to deepen the arbitrary model of Nizet and Pichault (2000)applied to the entrepreneurial configuration. To achieve this goal, we haveadopted an inductive qualitative approach, based on 17 semi-directiveinterviews, conducted with workshop owners.The results highlight the place of trust in human resource management,especially apprentices. Although these practices are described as informal,the integration of the apprentice into the workshop is based on theemployer's confidence in the child's accompanist; Trust is a guarantee ofquality training; the employer's interference in the apprentice's private lifeis not viewed negatively since the boss also provides the moral training ofthe apprentice. The delegation of responsibilities is often based on theemployer's confidence in the apprentice and sometimes on religiousbeliefs.
Keywords: African Research